Symposium 6: Problem-oriented project studies – the role of the teacher as supervising / facilitating the study group in its learning processes - Danielsen, Oluf; Nielsen, Jørgen Lerche (Proceedings of the International Conference on Networked Learning, 2010)
This contribution focuses on ’problem based learning’ (however we prefer the notion of ‘problem-oriented project studies’) and the role of the teacher in such a context. The classic traditional role as an expert deciding the curriculum, providing lectures and seminars, giving assignments and marking papers / essays is complemented and in some way overruled by a new role as supervisor and facilitator for the group of students working with a research problem, they themselves have picked. However different dimensions of this new teacher role can be seen – from expert in an academic field (result-oriented focusing on how the final product demonstrates the students’ ‘correct’ way to handle the academic aspects of the subject in mind) to a role more focusing on processes, methodological dimensions and stressing the importance of a reflexive approach. Some teachers may even tend to take on a role of a ‘therapist’, questioning and assisting the members of the group in the complex task of acting together with fellow students in an uncertain and volatile context and environment.